Au Nanochains Anchored on 3D Polyaniline/Reduced Graphene Oxide Nanocomposites as a High‐Performance Catalyst for Ethanol Electrooxidation. Issue 8 (8th May 2017) - Zhang, Ke; Shi, Yuting; Li, Shumin; Wang, Caiqin; Yan, Bo; Xu, Hui; Wang, Jin; Guo, Jun; Du, Yukou
Abstract: A nanocomposite containing Au, polyaniline (PANI) and reduced graphene oxide (RGO) has been synthesized by a two‐step method. The PANI can intermix with graphene to build a three‐dimensional (3D) structure, which is beneficial for uniform dispersion of Au networks with a mean diameter of 5.6 nm. In addition to its role as the support of Au, the presence of PANI is also favorable for avoiding the heavy agglomeration of graphene when the reduction occurs. Additionally, the introduction of graphene can not only boost the connections with PANI, but also accelerate the electron transfer between the electrolyte solution and catalysts. Electrochemical tests indicate that the Au/PANI/RGO hybrid exhibits high catalytic activity and stability for ethanol electrooxidation in alkaline conditions. The superior performance can be ascribed to the uniform dispersion of the Au nanocatalyst on the PANI/RGO support with a particular 3D structure, resulting in an increase of the electrochemically active surface area together with a synergic effect between the PANI, graphene and Au. Abstract : Combine and conquer : A 3D Au/polyaniline/RGO nanocomposite exhibits outstanding electrocatalytic performance toward the ethanol oxidation reaction. During the electrocatalysis process, ethanol is oxidized to acetate.